Possible role of WNT10B in increased proliferation and tubule formation of human umbilical vein endothelial cell cultures treated with hypoxic conditioned medium from human adipocytes - Pourdashti, Sara; Faridi, Nassim; Yaghooti, Hamid; Jalali, Mohammad-Taha; Soroush, Ahmadreza; Bathaie, S. Zahra (Biotechnic & histochemistry, 2022)
Regulation of angiogenesis plays an important role in adipose tissue expansion and function. The Wnt pathway and WNT10B, the main member of Wnt family, participate in angiogenesis in cancer tumors, but there is limited evidence to support the regulatory role of WNT10B in human adipose tissue angiogenesis. Subcutaneous white adipose tissue (scWAT) of 80 participants including obese and non-obese subjects was obtained and the expression of WNT10B and VEGFA genes were evaluated using qPCR. Human adipose-derived stem cells (hADSC) were differentiated to adipocytes and incubated under either hypoxic or normoxic conditions. The conditioned media of these adipocytes were collected and used as growth media for human umbilical vein endothelial cells (HUVEC) in Matrigel. We evaluated the proliferation, cell cycle phases, tubule formation and β-catenin activation of these treated cells. We found a significant correlation between WNT10B and VEGFA expression in the scWAT of both obese and non-obese subjects. Proliferation and tubule formation of HUVEC treated with conditioned media of hypoxic adipocytes (hCM) in the S-phase were increased significantly compared to the HUVEC treated with the conditioned media of normoxic adipocytes (nCM). The expression of WNT10B and VEGFA was enhanced in hypoxic adipocytes compared to normoxic adipocytes; also, activation and nuclear translocation of β-catenin was enhanced in the HUVEC treated with hCM compared to nCM. WNT10B acts as an angiogenic protein in scWAT under hypoxic conditions. Hypoxia induced WNT10B increases VEGFA expression and causes tube formation by HUVECs and angiogenesis in adipose tissue via the canonical Wnt/β-catenin pathway.